The Role of Labour Productivity in the Influence of E-HRM on Sustainability Performance with Organizational Agility as a Moderating Variable in MSMEs - Sentoso, Antony; Junestin, Junestin; Nelson, Alden (Almana : Jurnal Manajemen dan Bisnis, 2024)
In this era, technological advances benefit many aspects of work, including Human Resources Management (HRM). Implementing E-HRM helps organizations improve efficiency, reduce paper waste, and support sustainability principles. The study aims to examine the impact of E-HRM on Sustainability Performance, mediated by Labour Productivity and moderated by Organizational Agility. The research was conducted on MSMEs in Batam City, using a purposive sampling technique to obtain primary data from 200 respondents by distributing G-From questionnaires. The quantitative analysis method used is SmartPLS software. The research results of the hypothesis that shows a direct and significant positive effect on Sustainability Performance is Labor Productivity. Meanwhile, E-HRM implementation has a positive, not significant, effect on Sustainability Performance but has a positive, significant impact on Labour Productivity. The proven indirect research hypothesis is the relationship between E-HRM implementation and Sustainability Performance mediated by Labor Productivity. The theory that E-HRM implementation significantly positively affects Labour Productivity through moderation of organizational agility has yet to be proven. This research is expected to cover a broader range of research and can be used as a reference for other studies.